Legionella pneumophila Pneumonia in Pregnancy: A Case Report and Review of the Literature - Kleinberg, Katherine A.; Antony, Suresh J. (Infectious Disorders - Drug Targets, 2020)
L. pneumophila is an unusual cause of pneumonia with a prevalence of 2.7%, and it is even more uncommon in pregnancy. To date, only 11 cases of Legionnaire’s Disease in pregnancy have been reported, though this small number could possibly be attributed to underdiagnoses and under documentation. Case Presentation: In this paper, we present a 31-year-old Hispanic female, gravida 4, para 1 from the southwest United States who presented with a 3-week history of fever, worsening cough, dyspnea on exertion, and hypoxemia. Chest x-ray showed bibasilar infiltrates, with positive serology for Legionella IgM and IgG (1:250 and 1:640 respectively), as well as positive urinary antigen. Despite appropriate treatment with azithromycin 500 mg, she continued to have dyspnea and mild respiratory distress. Conclusion: Upon follow up, mother and fetus initially remained stable without any signs of sequelae from Legionnaire’s disease, but the patient miscarried 5 weeks after the second admission to the hospital. The chest x-ray eventually cleared up after almost 21 days of azithromycin.
Keywords: pregnancy